The use of the local environment for teaching geography : a case study in the Umtata administrative area - Adonis, Agrinette Nolwandle (Rhodes University, Faculty of Education, Department of Education, 1993)
Current theories in geographical education advocate the use of strategies that encourage the pupil to play an active role in learning, thereby making such learning more meaningful and effective. Fieldwork is perceived as one such method. Fieldwork helps pupils acquire and develop understanding of geographical concepts, skills, attitudes and values through their own efforts and involvement. Fieldwork approaches have tended to change with the changing paradigms resulting in the development of approaches that are more pupil and experience oriented. In the South African school geography curricula fieldwork has been explicit since 1985. However, research has shown that in most South African secondary schools fieldwork as a teaching strategy is only applied to a limited extent. Teachers have always used financial constraints and time limitations as explanations for their failure to use fieldwork in teaching geography. This study attempts to demonstrate how the local environment of any school can be used effectively for teaching and learning most aspects of the senior secondary school geography syllabus, thereby alleviating the problems of time and money perceived by teachers as the major constraints inhibiting their use of fieldwork. In order to illustrate the effectiveness of fieldwork in the local environment, this study incorporated an analysis of the current senior secondary school geography syllabus, the identification of potential fieldwork sites in the Umtata District and the development and implementation of three fieldwork units based on three of the sites identified. The analysis of the evaluations of the three fieldwork units by the researcher, the pupils and the non-participant observer revealed that fieldwork conducted in the local environment is highly effective, interesting and rewarding to pupils even when they have no prior experience of fieldwork.
Keywords: Geography -- Fieldwork -- Study and teaching; Geography -- South Africa -- Study and teaching (Secondary); Black people -- Education -- South Africa